ANALISIS RASIO AKTIVITAS DAN RASIO PROFITABILITAS SEBAGAI DASAR DALAM MENILAI KINERJA KEUANGAN PERUSAHAAN PADA PT SIANTAR TOP TBK. - TRIYANA NURAINI, AJENG (Jurnal Akuntansi AKUNESA, 2015)
The purpose of this study was to determine the company’s financial performance is calculated using the inventory turnover, total assete turnover, return on asset (ROA), and return on equity (ROE). This study is a quantitative descriptive study. Object od research is a component of financial statements Siantar Top. With the use of purposive sampling. Analysis technique is to calculate the average ratio an then interpret it. Inventory turnover ratio analysis results obtained industry average by 6 times. it can be said that the company is in good shape. total asset turnover ratio shows the industry average of 1.14 times. in this ratio indicates that the company is said to be in good condition. The next industry average ROA ratio obtained amount of 7%. This ratio is influenced by fluctuating income. ROE ratio with a value of 12.46% said that the company's performance is quite good. Based on the analysis by using the inventory turnover, total asset turnover, return on asset (ROA), and return on equity (ROE). The company’s financial performance can be know and in good condition.   Keyword: Activity Ratio, Profitability Ratio, Financial Performance